Analisis Penerimaan Aplikasi Ajaib dengan Menggunakan Technology Acceptance Model 3 (TAM 3) - Muhammad Arya Wirawan; Abdul Yusuf; Ady Wahyono (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to quantitatively test the acceptance of the Magic application in the community by using the Techonology Acceptance Model 3, the sample of this study is the user of the Magic application, the sample is carried out using a simple random sampling method. Data was collected by distributing questionnaires using a Likert scale for assessment. The results of this study indicate that of the 17 hypotheses, there are 4 hypotheses that are accepted because they have a p-value <0.5, namely BI -> UB, EXP -> PU, PE-> PEOU and PU -> BI variables. The remaining 13 hypotheses were rejected or had no effect because they had a p-value > 0.05.